Analisis Korelasi Implementasi Layanan Pesan Antar Berbasis Aplikasi Terhadap Penjualan Kafe Di Masa Pandemi Covid-19: Studi Kasus OCD Coffee Shop - Adhiguna, Erlangga Tri; Mahdi, Muhammad Fattah; Fauzan, Muhammad Nepo; Rabbani, Zonar Anjab; Santoso, Sugeng (Journal Industrial Manufacturing, 2021)
This research was conducted to analyze the effect of implementation of delivery application with sales of a cafe during COVID-19 pandemic with a case study of the OCD Coffee Shop. This research is a type of explanatory research, with qualitative and quantitative approach, used 3137 customers as a sample with cluster sampling methods from thousand customers in population. The primer data of this research obtained by interviewing couple informant including key and supporting. The data obtained was analyzed using normality test, linear test, and correlation test between variables. The conclusion of this study is implementation of delivery application has a significant effect on sales and brings positive impact beside economy.Key Words: Delivery Application, Sales, COVID-19 Pandemic